Het volkskind : zijne opvoeding en zijn onderwijs. - Lievevrouw-Coopman, M. (Gent : s.l., 1895)
Collectie Vrijzinnige Werkmansbibliotheek
Nederlands
Monografie
Keywords: Vrijzinnige Werkmansbibliotheek